A Cr5Si3 non-layered two-dimensional material and its preparation and application
By using the combined control of pure silicon wafers and CrCl3 powder during the CVD preparation process, combined with the induction effect of SiO2/Si tablets, Cr5Si3 non-layered two-dimensional material with excellent magnetic properties was successfully prepared, which solved the preparation in the prior art The problem of unsatisfactory accumulation and crystallinity of raw materials during the process has achieved high quality and controllability of the material.
Patent Information
- Application Number
- CN202310061611.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-18
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-01-18
AI Technical Summary
It is difficult to prepare chromium silicide non-layered two-dimensional materials with excellent magnetic properties in the prior art, especially during the preparation of CVD, where raw materials are prone to accumulate in the vertical direction and unsatisfactory crystallinity.
Using pure silicon wafers as the silicon source, combined with the combined control of the ratio of CrCl3 powder and pure silicon wafer, the volatilization temperature of raw materials and the deposition temperature, Cr5Si3 non-layered two-dimensional material was successfully prepared by chemical vapor deposition method, and through SiO2/ Compound SiO2/Si sheets on Si substrates are used to induce the deposition of Cr5Si3 two-dimensional material and improve its morphology and crystallinity.
It realizes high-quality preparation of Cr5Si3 non-layered two-dimensional material, with excellent air stability and topological Hall effect performance, and is also controllable in thickness and regular morphology, which is suitable for exploring its special properties on the two-dimensional scale.
Smart Images

Figure CN116040636B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nanomaterials, and specifically relates to the preparation of chromium silicide non-layered two-dimensional materials and the characterization of their magnetic properties. Technical Background
[0002] In today's era, the total amount of digital information storage has exploded, and the amount of electricity consumed by data storage is increasing, which places higher demands on the performance of information storage devices. However, traditional spin electronics devices based on ferromagnetic materials are easily disturbed by external magnetic fields due to the presence of macroscopic magnetic moments in ferromagnets, and the interference of stray fields does not allow storage units to be closely arranged, limiting the high-density integration of storage units. In contrast, in antiferromagnets, adjacent magnetic moments are parallel and arranged in opposite directions, showing a zero net magnetic moment. Therefore, they have strong stability to magnetic field disturbances and generate very little stray fields, so high-density storage integration can be achieved. [1-3] At the same time, the spin configurations of antiferromagnetic materials are diverse, among which non-collinear antiferromagnets with non-trivial spin structures can produce unconventional electromagnetic responses. [4-7] When current flows through the non-collinear spin structure, the three adjacent spins (S i , S j and S k ) produces a non-zero scalar spin chirality S i ·(S j ×S k ), which can induce a non-zero Berry curvature in real space, acting as a virtual magnetic field on conduction electrons, thus producing the topological Hall effect (THE) [8-14] .
[0003] Compared with traditional three-dimensional (3D) magnetic materials, two-dimensional (2D) magnetic materials have the advantages of large surface area, no dangling bonds on the surface, weak interlayer coupling, sensitivity to external physical fields, and easy construction of van der Waals heterostructures. They are one of the best candidate materials for the new generation of spin electronics and magnetic memory devices. In recent years, two-dimensional magnetic materials have been widely studied due to their ultra-thin thickness and rich physical properties. [15-23] . Silicide has good lattice matching with silicon substrate. Silicide obtained by epitaxy on silicon substrate has higher crystal quality, can form a sharp interface with silicon substrate, and has better structure and thermal stability. Therefore, silicon compounds have good compatibility with current silicon-based CMOS technology. Although silicide has many excellent properties, research based on the magnetism of silicide is still rare. The main reason is that most of the bulk materials of transition metal silicides are not magnetic.
[0004] <h2 style=";text-align:left;direction:ltr">[1]Y.Takeuchi,Y.Yamane,J.-Y.Yoon,R.Itoh,B.Jinnai,S.Kanai,JiIeda,S.Fukami,H.Ohno,Nat.Mater.2021,20,1364.<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">
[0005] <h2 style=";text-align:left;direction:ltr"> [2] M.Kimata, H.Chen, K.Kondou, S.Sugimoto, P.K.Muduli, M.Ikhlas, Y.Omori, T.Tomita, A.H.MacDonald, S.Nakatsuji, Y.Otani, Nature 2019, 565, 627.<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">
[0006] <h2 style=";text-align:left;direction:ltr"> [3] B.A.Bernevig,C.Felser,H.Beidenkopf,Nature 2022,603,41.<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">
[0007] <h2 style=";text-align:left;direction:ltr"> [4]N.Kiyohara,T.Tomita,S.Nakatsuji,Phys.Rev.Appl.2016,5,064009.<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">
[0008] <h2 style=";text-align:left;direction:ltr"> [5] Y.Shiomi,M.Mochizuki,Y.Kaneko,Y.Tokura,Phys.Rev.Lett.2012,108,056601.<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">
[0009] <h2 style=";text-align:left;direction:ltr"> [6] Y.Machida,S.Nakatsuji,Y.Maeno,T.Tayama,T.Sakakibara,S.Onoda,Phys.Rev.Lett.2007,98,057203.<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">
[0010] <h2 style=";text-align:left;direction:ltr"> [7]<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">
[0011] <h2 style=";text-align:left;direction:ltr"> [8] K.Ueda, S.Iguchi, T.Suzuki, S.Ishiwata, Y.Taguchi, Y.Tokura, Phys.Rev.Lett.2012,108,156601.<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">
[0012] <h2 style=";text-align:left;direction:ltr"> [9]P.Bruno,V.K.Dugaev,M.Taillefumier,Phys.Rev.Lett.2004,93,096806.<h2 style=";text-align:left;direction:ltr">
[0013]
[10] G.Metalidis,P.Bruno,Phys.Rev.B 2006,74,045327.
[0014]
[11] H.Li,B.Ding,J.Chen,Z.Li,E.Liu,X.Xi,G.Wu,W.Wang,Appl.Phys.Lett.2020,116,182405.
[0015]
[12] Y.Chen,Y.-W.Chuang,SHLee,Y.Zhu,K.Honz,Y.Guan,Y.Wang,K.Wang,Z.Mao,J.Zhu,C.Heikes,P.Quarterman,P.Zajdel,JABorchers,W.Ratcliff.46,Ma14.20v.
[0016]
[13] T.Kurumaji,T.Nakajima,M.Hirschberger,A.Kikkawa,Y.Yamasaki,H.Sagayama,H.Nakao,Y.Taguchi,T.-h.Arima,Y.Tokura,Science 2019,365,914.
[0017]
[14] P.Chen,C.Zhang,Y.Wang,B.Lv,P.Liu,Y.Tian,J.Ran,C.Gao,Q.Liu,D.Xue,Phys.Rev.B 2021,104,064409.
[0018]
[15] B.Huang,G.Clark,E.Navarro-Moratalla,DRKlein,R.Cheng,KLSeyler,D.Zhong,E.Schmidgall,MAMcGuire,DHCobden,W.Yao,D.Xiao,P.Jarillo-Berrero,X.Xu7,Nature
[0019]
[16] C.Gong,L.Li,Z.Li,H.Ji,A.Stern,Y.Xia,T.Cao,W.Bao,C.Wang,Y.Wang,ZQQiu,RJCava,SGLouie,J.Xia,X.Zhang,Nature 2017,546,265.
[0020]
[17] Y. Deng, Y. Yu, Y. Song, J. Zhang, N. Z. Wang, Z. Sun, Y. Yi, Y. Z. Wu, S. Wu, J. Zhu, J. Wang, X. H. Chen, Y. Zhang, Nature 2018, 563, 94.
[0021]
[18] B. Li, Z. Wan, C. Wang, P. Chen, B. Huang, X. Cheng, Q. Qian, J. Li, Z. Zhang, G. Sun, B. Zhao, H. Ma, R. Wu, Z. Wei, Y. Liu, L. Liao, Y. Ye, Y. Huang, X. Xu, X. Duan, W. Ji, X. Duan, Nat. Mater. 2021, 20, 818.
[0022]
[19] B. Tang, X. Wang, M. Han, X. Xu, Z. Zhang, C. Zhu, X. Cao, Y. Yang, Q. Fu, J. Yang, X. Li, W. Gao, J. Zhou, J. Lin, Z. Liu, Nat. Electron. 2022, 5, 224.
[0023]
[20] J. Zhou, W. Zhang, Y.-C. Lin, J. Cao, Y. Zhou, W. Jiang, H. Du, B. Tang, J. Shi, B. Jiang, X. Cao, B. Lin, Q. Fu, C. Zhu, W. Guo, Y. Huang, Y. Yao, S. S. P. Parkin, J. Zhou, Y. Gao, Y. Wang, Y. Hou, Y. Yao, K. Suenaga, X. Wu, Z. Liu, Nature 2022, 609, 46.
[0024]
[21] Y. Deng, Y. Yu, M. Z. Shi, Z. Guo, Z. Xu, J. Wang, X. H. Chen, and Y. Zhang, Science 2020, 367, 895.
[0025]
[22] H.Jiang,P.Zhang,X.Wang,Y.Gong,Nano Res.2021,14,1789.
[0026]
[23] J.Zhou,J.Lin,X.Huang,Y.Zhou,Y.Chen,J.Xia,H.Wang,Y.Xie,H.Yu,J.Lei,D.Wu,F.Liu,Q.Fu,Q.Z eng,C.-H.Hsu,C.Yang,L.Lu,T.Yu,Z.Shen,H.Lin,BIYakobson,Q.Liu,K.Suenaga,G.Liu,Z.Liu,Nature 2018,556,355. Summary of the invention
[0027] The first purpose of the present invention is to provide a Cr5Si3 non-layered two-dimensional material, aiming to provide a new material with excellent performance.
[0028] The second purpose of the present invention is to provide a Cr5Si3 two-dimensional material with controllable thickness obtained by the preparation method.
[0029] The third object of the present invention is to provide the application of Cr5Si3 nanosheets of different thicknesses obtained by the preparation method, and to explore the magnetic properties related to the thickness of Cr5Si3.
[0030] A Cr5Si3 non-layered two-dimensional material, which is a Cr5Si3 non-layered single crystal two-dimensional material.
[0031] The present invention provides a new Cr5Si3 non-layered two-dimensional material, and the new material has excellent new properties, for example, it has excellent air stability and is conducive to showing an excellent topological Hall effect.
[0032] Preferably, its thickness is 3.8-45nm, preferably 13-35nm, and further preferably 14-20nm; the present invention unexpectedly discovered that for Cr5Si3 non-layered two-dimensional materials, there is a special correlation between its thickness and magnetic properties, and within the preferred thickness range, it can unexpectedly exhibit excellent topological Hall effect.
[0033] Preferably, the plane size of the Cr5Si3 non-layered two-dimensional material (referring to the extension distance of the Cr5Si3 on the substrate plane) is 2-50 μm.
[0034] Preferably, the morphology of the Cr5Si3 non-layered two-dimensional material is mostly regular hexagons.
[0035] The present invention also provides a method for preparing the Cr5Si3 non-layered two-dimensional material, wherein CrCl3 powder and pure silicon wafer are heated and volatilized, and the Cr5Si3 non-layered two-dimensional material is formed by chemical deposition on a substrate in a protective carrier gas atmosphere;
[0036] The mass ratio of the CrCl3 powder to the pure silicon wafer is 2:1 to 0.5:1;
[0037] The volatilization temperature of the CrCl3 powder is 650-770°C;
[0038] The volatilization temperature of the pure silicon wafer is 980-1060°C;
[0039] The temperature of chemical vapor deposition is 980-1060°C.
[0040] The present invention proposes for the first time a CVD-based method for synthesizing Cr5Si3 materials. However, studies have found that in order to successfully realize the CVD preparation of Cr5Si3 materials, many technical problems need to be faced, such as the problem that raw materials are easy to accumulate in the vertical direction and it is difficult to obtain non-layered two-dimensional materials, and the problem that the crystallinity of Cr5Si3 is not ideal. In response to the difficulties faced by the CVD preparation of the materials of the present invention, the present invention innovatively uses pure silicon wafers as the silicon source, and cooperates with the ratio of CrCl3 powder and pure silicon wafers, the volatilization temperature of the raw materials and the deposition temperature to achieve synergy. It can realize the preparation of Cr5Si3 non-layered two-dimensional material single crystals for the first time in the industry. In addition, it can also improve the growth behavior of the material and improve its performance.
[0041] In the present invention, based on pure silicon wafers as silicon sources, combined with the volatilization temperature of the raw material sources, the deposition temperature and the proportional relationship between the raw material sources, synergy can be achieved, and the preparation of Cr5Si3 non-layered two-dimensional materials can be unexpectedly successfully realized. Not only that, it is also beneficial to improve the morphology of the material and improve its performance.
[0042] In the present invention, the volatilization temperature of the CrCl3 powder can be understood as the temperature of the CrCl3 powder source, which is preferably 710-740°C.
[0043] In the present invention, the protective carrier gas is at least one of nitrogen and an inert gas;
[0044] Preferably, in the chemical vapor deposition stage, the flow rate of the protective carrier gas is 10 to 200 sccm, and can further be 20 to 100 sccm.
[0045] In the present invention, the substrate is a SiO2 / Si substrate.
[0046] Preferably, in the SiO2 / Si substrate, the thickness of the SiO2 layer is 50 to 2000 nm, preferably 100 to 500 nm.
[0047] The present invention has found that in the process of CVD synthesis of Cr5Si3 non-layered two-dimensional materials, Cr5Si3 nanosheets tend to grow on the edge of the substrate, which will affect the growth morphology to a certain extent and affect the subsequent device preparation. In response to the difficult problem faced by the CVD preparation of the new material described in the present invention, the present invention has further found through research that SiO2 / Si sheets (induced sheets) are innovatively compounded on the surface of the SiO2 / Si substrate. In this way, the Cr5Si3 two-dimensional material can be unexpectedly induced to grow in the area and edge where the SiO2 / Si sheets are compounded, so that the deposition position of the two-dimensional material can be artificially induced, and the preparation morphology, crystallinity and performance of the prepared material can be improved.
[0048] In the present invention, the size of the induction sheet is smaller than the sheet size of the substrate, and preferably can be 10-50% of the plane size of the substrate.
[0049] In the present invention, the SiO2 / Si sheet can be a material of any properties, and can be composited on the surface of the substrate in any form.
[0050] In the present invention, the volatilization temperature of the pure silicon wafer can be understood as the temperature of the area where the pure silicon wafer is placed, which is preferably 1010-1050°C; it can be further preferably 1020-1030°C; preferably, the temperature in the chemical vapor deposition stage can be understood as the temperature of the area where the substrate is placed, which is preferably 1010-1050°C, and can be further preferably 1020-1030°C. The present invention has found that under the process, further combined control of the volatilization of the pure silicon wafer and the deposition temperature of the substrate is further coordinated, which is beneficial to improve the phase purity, morphology, and crystallinity of Cr5Si3, and not only that, but also to improve the topological Hall effect of the prepared material.
[0051] Preferably, the temperature difference between volatilization and chemical vapor deposition of the pure silicon wafer is less than or equal to 5° C., and preferably the same.
[0052] Preferably, the chemical vapor deposition time is 2-10 min, more preferably 2-5 min.
[0053] In the present invention, the deposition device for implementing the preparation method comprises a sealed quartz tube, one end of the quartz tube is provided with an inlet for inputting carrier gas into the quartz tube chamber, and the other end is provided with an outlet for outputting the gas in the quartz tube chamber; according to the direction of the carrier gas flow, the chamber of the quartz tube is divided into an upstream variable temperature zone and a downstream high-temperature constant temperature zone; the high-temperature constant temperature zone is provided with a heating device, characterized in that a magnetic boat loaded with CrCl3 powder is placed in the upstream variable temperature zone, and a magnetic boat loaded with pure silicon wafers and SiO2 / Si substrates is placed in the downstream high-temperature constant temperature zone;
[0054] During the preparation process, CrCl3 powder and pure silicon wafers are heated to the volatilization temperature under the action of protective gas as carrier gas, and the temperature of the downstream high-temperature constant temperature zone is controlled within the chemical deposition temperature range, so that the volatilized CrCl3 powder and pure silicon wafer raw materials react with each other and are deposited on the SiO2 / Si substrate, and Cr5Si3 non-layered two-dimensional material is grown on the SiO2 / Si substrate.
[0055] In addition to being the first in the industry to successfully prepare Cr5Si3 nanosheets using chemical vapor deposition, the present invention also innovatively prepares Cr5Si3 nanosheets with a thickness as thin as 3.8nm, a size of 2-50μm, and good morphology and crystallization properties. The preparation of Cr5Si3 nanosheets by the present invention provides a basis for exploring their special properties on a two-dimensional scale and provides proof for the reliability of theoretical research. The method of the present invention is simple to operate, and the prepared nanosheets have controllable thickness, regular shape, and are high-quality single crystals.
[0056] The present invention also includes two methods for testing the magnetic properties of Cr5Si3 nanosheets. The Cr5Si3 nanosheets are grown on a SiO2 / Si substrate using the Cr5Si3 nanosheet preparation method, and the magnetic anisotropy of the Cr5Si3 nanosheets of different thicknesses is tested using a vibrating sample magnetometer (VSM).
[0057] High-quality Cr5Si3 nanosheets of different thicknesses were prepared using the Cr5Si3 nanosheet preparation method, Hall devices of different thicknesses were made using electron beam exposure, and the magnetic transport properties of the obtained Cr5Si3 nanosheets were tested using a comprehensive physical property measurement system (PPMS).
[0058] The present invention also includes the application of the Cr5Si3 non-layered two-dimensional material to prepare a Hall device.
[0059] Beneficial Effects
[0060] 1. The present invention provides a new Cr5Si3 non-layered two-dimensional material, which has excellent air stability and is also conducive to obtaining a high topological Hall effect.
[0061] 2. The present invention provides for the first time an idea for synthesizing Cr5Si3 non-layered two-dimensional materials based on the CVD method, and innovatively uses pure silicon wafers as raw materials, and cooperates with the joint control of the amount of pure silicon wafers, the volatilization temperature of the raw materials and the deposition temperature, which can solve the problems faced by the CVD preparation of the new materials of the present invention, and can obtain pure Cr5Si3 phase, a new material with high cleanliness, high crystallinity and excellent morphology; not only that, the present invention further cooperates with the use of silicon induction sheets to induce the deposition of Cr5Si3 non-layered two-dimensional materials, improve deposition behavior and effects, and facilitate the acquisition of new materials with high air stability and topological Hall effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1 Schematic diagram of atmospheric pressure chemical vapor deposition apparatus for preparing Cr5Si3 nanosheets;
[0063] Figure 2 The atomic structure diagram of the Cr5Si3 nanosheet prepared in Example 1;
[0064] Figure 3 This is the EDS image of the Cr5Si3 nanosheets prepared in Example 1;
[0065] Figure 4 This is a planar STEM image of the Cr5Si3 nanosheets prepared in Example 1;
[0066] Figure 5 This is a cross-sectional STEM image of the Cr5Si3 nanosheet prepared in Example 1;
[0067] Figure 6 This is an optical picture of the Cr5Si3 nanosheets obtained in Example 1;
[0068] Figure 7 This is a diagram showing the distribution of Cr5Si3 nanosheets on the surface of SiO2 / Si substrate in Example 1;
[0069] Figure 8 This is an optical picture of the Cr5Si3 nanosheets obtained in Example 1 after being stored in air;
[0070] Fig. 9 This is an optical picture of the Cr5Si3 nanosheets obtained in Example 2;
[0071] Fig.10 This is an optical picture of the Cr5Si3 nanosheets obtained in Example 3;
[0072] Fig.11 This is an optical picture of the Cr5Si3 nanosheets obtained in Example 4;
[0073] Fig.12 This is an optical picture of the Cr5Si3 nanosheets obtained in Example 5;
[0074] Fig.13 This is an optical picture of the Cr5Si3 nanosheets obtained in Comparative Example 1;
[0075] Fig.14 , Fig.15 , Fig.16 The magnetic measurement data of Cr5Si3 nanosheets obtained in Example 6;
[0076] Fig.17 This is a graph showing the magnetic transport test data of the Cr5Si3 nanosheet device obtained in Example 7; Specific implementation methods
[0077] The present invention is further described below through implementation cases, but the content of the present invention is not limited to the following content.
[0078] Schematic diagram of the vapor deposition device for preparing Cr5Si3 nanosheets is shown in Figure 1 , including a quartz tube 1; an upstream variable temperature zone 2, a porcelain boat loaded with CrCl3 powder; a downstream constant temperature zone 3, loaded with pure silicon wafers and SiO2 / Si silicon wafers with the polished surface facing upward. The device is also provided with a heating device for heating the high temperature constant temperature zone. Both ends of the quartz tube 1 are provided with air holes, wherein the air hole at the left end of the quartz tube 1 (upstream of the carrier gas) is the air inlet hole, and the air hole at the right end of the quartz tube 1 is the air outlet hole.
[0079] The present invention has no special requirements on the particle size of the raw materials. Unless otherwise specified, the raw materials used in the following examples and comparative examples are:
[0080] CrCl3, provided by Elfa Aisha, with a purity greater than 99.99%.
[0081] Example 1
[0082] Preparation of Cr5Si3 nanosheets:
[0083] Place the porcelain boat containing CrCl3 powder in the upstream variable temperature zone (temperature zone 2) of the tube furnace, and place the porcelain boat containing pure silicon wafers and 285nm SiO2 / Si silicon wafers with the polished surface facing up in the center of the downstream constant temperature zone (285nm SiO2 / Si is used as the growth substrate for Cr5Si3. The mass of CrCl3 powder is 0.1g, and the mass of pure silicon wafer is 0.2g). Before heating, use a large flow of argon to exhaust the air in the quartz tube. Then control the temperature of constant temperature zone 2 at 730°C (marked as T1, the volatilization temperature of CrCl3 powder), and the temperature of temperature zone 3 at 1010°C (marked as T2, which is the volatilization and vapor deposition temperature of the silicon wafer), and perform constant temperature deposition for 3 minutes (holding time at the deposition temperature) at an argon flow rate of 30sccm. Single crystal Cr5Si3 nanosheets will be generated on the silicon wafer. The experimental setup of Cr5Si3 nanosheets is shown in the figure below. Figure 1 The atomic structure diagram, EDS, planar STEM image and optical photo of the prepared Cr5Si3 nanosheets are shown in Figure 2 , 3, 4, 5 and 6. The distribution of Cr5Si3 nanosheets on the surface of SiO2 / Si substrate is shown in Figure 7 shown.
[0084] Figure 3EDS shows that the Cr5Si3 nanosheets we synthesized contain only two elements, Cr and Si, and the ratio is about 1.67:1, which is consistent with the stoichiometric ratio of Cr to Si in Cr5Si3 nanosheets. Figure 4 The high-resolution STEM image of the synthesized Cr5Si3 nanosheets shows that the nanosheets contain only two elements, Cr and Si, and are consistent with the atomic structure of Cr5Si3. Figure 5 This is a high-resolution STEM image of a cross section of a Cr5Si3 nanosheet cut perpendicularly and parallel to the edge of the nanosheet. It is consistent with the atomic structure of Cr5Si3 in both directions. From the image, we can get the lattice constant of Cr5Si3. Figure 6 This is an optical schematic diagram of the prepared Cr5Si3 nanosheets. The SiO2 / Si substrate is light red, and the purple-red hexagons represent Cr5Si3 nanosheets with uniform thickness distribution. The Cr5Si3 nanosheets obtained under this condition have good crystallinity, a thickness of 4-6nm, and a size of 5-8μm. Figure 6 The scale bar in the figure is 10 μm. Figure 7 Figure 3 shows the distribution of Cr5Si3 nanosheets on the surface of SiO2 / Si substrate. Cr5Si3 nanosheets tend to be deposited at the edge of SiO2 / Si substrate, and almost no Cr5Si3 nanosheets are deposited in the middle of SiO2 / Si substrate, and a small amount of impurities are generated. Figure 7 The scale bar in the figure is 10 μm.
[0085] The thinner nanosheets among the samples grown in Example 1 are selected. Figure 8 As shown in the figure, the thickness of the selected nanosheets measured by atomic force microscopy was 5.7nm, the surface was uniform, and no impurities were adsorbed. After being placed in the air for 0 days, 3 days and 7 days, the atomic force microscopy was used to measure and it was found that the surface was still very clean and there was basically no change in thickness, proving that the Cr5Si3 nanosheets had not been degraded, had not adsorbed impurities, and had extremely high crystal quality. Figure 8 The scale bar in the figure is 10 μm.
[0086] Example 2
[0087] Compared with Example 1, the difference is that the temperature of T2 is changed to 970°C, 1030°C, 1050°C, and 1070°C respectively; other operations and parameters are the same as Example 1.
[0088] Fig. 9This is an optical schematic diagram of Cr5Si3 nanosheets prepared at different T2 temperatures. The SiO2 / Si substrate is light red, the purple hexagons are Cr5Si3, and the white hexagons are also Cr5Si3. When the T2 temperature is 970℃, the grown nanosheets are very small with a thickness of 14-18nm, and there is CrCl3 attached to the SiO2 / Si substrate (blue-green substance); when the temperature exceeds 970℃, the SiO2 / Si substrate becomes clean. The thickness of the nanosheets grown at 1030℃ is 18-20nm; the thickness of the nanosheets grown at 1050℃ is 35-40nm; the thickness of the nanosheets grown at 1070℃ is 150nm, which exceeds the two-dimensional size. Fig. 9 The scale bar in the figure is 10 μm.
[0089] Example 3
[0090] Compared with Example 1, the only difference is that the temperature of T1 is changed to 640°C, 710°C, 740°C, and 770°C respectively. Other operations and parameters are the same as Example 1.
[0091] The deposition of Cr5Si3 nanosheets on SiO2 / Si substrate at different CrCl3 volatilization temperatures (T1 temperature) was observed by optical microscopy. Fig.10 As shown in the figure, when the CrCl3 volatilization temperature (T1 temperature) is low (640℃), the quality of the Cr5Si3 nanosheets grown on the SiO2 / Si substrate is poor due to the low Cr content in the gas phase; as the CrCl3 volatilization temperature (T1 temperature) gradually increases, the Cr content in the gas phase gradually increases, and the quality of the Cr5Si3 nanosheets grown improves. The thickness of the Cr5Si3 nanosheets grown at the CrCl3 volatilization temperature (T1 temperature) of 690℃ is about 8-10nm; the thickness of the Cr5Si3 nanosheets grown at the CrCl3 volatilization temperature (T1 temperature) of 740℃ is about 16-18nm; the thickness of the Cr5Si3 nanosheets grown at the CrCl3 volatilization temperature (T1 temperature) of 770℃ is larger, about 70-75nm. Fig.10 The scale bar in the figure is 10 μm.
[0092] Example 4
[0093] Compared with Example 1, the only difference is that an induction sheet is used to induce deposition, and the steps are as follows:
[0094] The size of the SiO2 / Si substrate is 2×2 cm 2 , place three 0.1×2cm 2 The strip SiO2 / Si substrate (induction sheet) and other operations and parameters are the same as those in Example 1.
[0095] Fig.11This is an optical schematic diagram of Cr5Si3 nanosheets grown on SiO2 / Si substrates. From the optical images, it can be found that Cr5Si3 nanosheets are not only deposited on the edge of the SiO2 / Si substrate, but also deposited near the strip SiO2 / Si substrate (induction sheet). By adding a strip SiO2 / Si substrate (induction sheet), Cr5Si3 nanosheets can be grown in the middle of the SiO2 / Si substrate. Fig.11 The scale bar in the figure is 10 μm.
[0096] Example 5
[0097] Compared with Example 1, the only difference is that the mass ratio of chromium chloride (the amount remains unchanged) and pure silicon wafer is changed to: A=4:1; B=3:1; C=2:1; D=1:1, and other operations and parameters are the same as Example 1.
[0098] Fig.12 The optical schematic diagram of Cr5Si3 nanosheets prepared under different chromium chloride and pure silicon wafer mass ratios. When the chromium chloride and pure silicon wafer mass ratio is greater than or equal to 3:1, the Cr5Si3 nanosheets are partially etched and the yield of Cr5Si3 nanosheets is low. When the chromium chloride and pure silicon wafer mass ratio is 0.5 to 2:1, a large amount of Si can be continuously volatilized into the gas phase. The sufficient and stable supply of Si in the gas phase promotes the growth of high-quality and thin Cr5Si3 nanosheets. Fig.12 The scale bar in the figure is 10 μm.
[0099] Comparative Example 1
[0100] Compared with Example 1, the only difference is that an equal weight of silicon powder is used to replace the silicon wafer as the silicon source, and 0.05 g of NaCl is added to the silicon powder to assist the volatilization of the silicon powder. Other operations and parameters are the same as in Example 1.
[0101] Fig.13 This is an optical schematic diagram of the prepared Cr5Si3 nanosheets. The SiO2 / Si substrate is light red, the white hexagons on the SiO2 / Si substrate are thicker Cr5Si3 nanosheets, and the black ones are impurities from the reaction, indicating that when silicon powder is used as the raw material, the reaction is more violent, the grown Cr5Si3 nanosheets are thicker, and many impurities are produced. Therefore, silicon powder is not suitable as a Si source to grow Cr5Si3 nanosheets. Fig.13 The scale bar in the figure is 50 μm.
[0102] Example 6
[0103] Magnetic anisotropy test of Cr5Si3 with different thicknesses grown on silicon wafers. According to the growth conditions of Examples 1 and 2, the Cr5Si3 nanosheets with overall average thicknesses of 6.0nm, 13.0nm, 19.0nm, 27.0nm and 40.0nm were obtained at deposition temperatures of 1010°C, 1020°C, 1030°C, 1040°C and 1050°C, respectively. VSM tests were performed under parallel and perpendicular external magnetic field conditions at a temperature of 3K to obtain MH curves in two directions. The effective magnetic anisotropy constant K can be calculated based on the MH curves of nanosheets of different thicknesses under parallel and perpendicular external magnetic field conditions at 3K. eff , by comparing K eff The value can be used to determine the change in magnetic anisotropy of nanosheets of different thicknesses. In order to eliminate the influence of SiO2 / Si substrate on magnetic testing, the MH curve of pure SiO2 / Si substrate at 3K was tested respectively ( Fig.14 ), are all antimagnetic backgrounds, which can exclude the influence of the growth substrate on the magnetic test.
[0104] Fig.15 The sample holder is set for VSM test under parallel and perpendicular magnetic fields. The sample is cut into two pieces of 2×2 mm 2 For the VSM test of parallel magnetic field, a quartz sample rod is used to fix the sample in the specified position with low temperature glue for testing ( Fig.15 a). The VSM test in the vertical magnetic field uses a copper sample guide rod. Two samples are placed vertically on the copper guide rod using low-temperature glue and fixed with a clean capsule for testing ( Fig.15 b).
[0105] Fig.16ae are the MH curves of Cr5Si3 nanosheets with thickness of 6.0nm (deposition temperature of 1010℃), 13.0nm (deposition temperature of 1020℃), 19.0nm (deposition temperature of 1030℃), 27.0nm (deposition temperature of 1040℃) and 40.0nm (deposition temperature of 1050℃) respectively, after deducting the antimagnetic background of silicon wafer at 3K in the direction of parallel and perpendicular magnetic field. As can be seen from the figure, when the thickness is 6.0nm, under the perpendicular magnetic field (H⊥c-axis), the MH curve shows obvious ferromagnetic behavior, while under the parallel magnetic field (H∥c-axis), the MH curve and the external magnetic field are almost linear, indicating that it is paramagnetic in this direction, indicating that the Cr5Si3 nanosheets at 6.0nm show strong perpendicular anisotropy. With the increase of thickness (from 13.0nm to 19.0nm), the magnetism in the parallel direction gradually increases, but it still shows paramagnetism overall, indicating that the magnetic anisotropy gradually weakens. As the thickness further increases (from 19.0nm to 27.0nm), the magnetism in the parallel direction gradually weakens. When the thickness reaches 40.0nm, the MH curve in the parallel direction has almost no hysteresis phenomenon, indicating that the magnetic anisotropy gradually increases. Fig.16 f calculated the effective magnetic anisotropy constant (K eff ) value, and its changing trend is consistent with the conclusion obtained from the observation of the hysteresis loop: with the increase of thickness, the magnetic anisotropy of Cr5Si3 nanosheets first weakens and then increases, and the magnetic anisotropy is weakest when the thickness is about 19.0nm.
[0106] Example 7
[0107] Hall devices were made from nanosheets of different thicknesses, and magnetic transport tests were performed at 3K.
[0108] According to the growth conditions of Examples 1 and 2, nanosheets are obtained at deposition temperatures of 1010°C, 1020°C, 1030°C, 1040°C, and 1050°C. Optical images and atomic force microscopy are used to determine the thickness of Cr5Si3 nanosheets of 6.0nm (deposition temperature of 1010°C), 13.0nm (deposition temperature of 1020°C), 19.0nm (deposition temperature of 1030°C), 27.0nm (deposition temperature of 1040°C), and 40.0nm (deposition temperature of 1050°C). Electron beam exposure is used to make Hall devices for nanosheets with determined thicknesses under different deposition temperature conditions, such as selecting 6.5nm nanosheets deposited at 1010°C, 14.2nm nanosheets deposited at 1020°C, 19.6nm nanosheets deposited at 1030°C, 24.3nm nanosheets deposited at 1040°C, and 36.0nm nanosheets deposited at 1050°C, and 10 / 50nm nanosheets are evaporated. In / Au, magnetotransport tests of devices of various thicknesses were performed at 3K. Fig.17is the ρ of the samples with thicknesses of 6.5nm, 14.2nm, 19.6nm, 24.3nm, and 36.0nm when the external magnetic field is parallel to the ab plane at 3K xy / / -H curve. When the thickness is greater than 6.5nm, the topological Hall effect begins to appear. When the thickness continues to increase to 19.6nm, the topological Hall effect intensity is the largest. When the thickness continues to increase to 24.3nm, the topological Hall effect intensity gradually weakens. When the thickness reaches 36.0nm, the topological Hall effect gradually disappears. Combined with the magnetic anisotropy intensity of Cr5Si3 nanosheets of different thicknesses in Example 6, it can be seen that the topological Hall effect can only be detected under the appropriate magnetic anisotropy intensity. Corresponding to Fig.16 K in f eff value, only when K eff< 2.5×10 5 erg / cm 3 hour( Fig.16 K in the blue range of f eff At a strong magnetic anisotropy strength, the long-range ordered non-collinear magnetic structure of Cr5Si3 is destroyed, and the topological Hall effect cannot be measured.
[0109] Through the above examples and comparative examples, it is found that the successful preparation of Cr5Si3 two-dimensional materials requires the coordinated control of the type of raw materials, the volatilization temperature of the raw materials, the carrier gas flow rate, and the deposition temperature of the volatilized material within the described range. In the present invention, under the coordination of the type of material, the deposition temperature (also called the growth temperature) and the carrier gas flow rate, Cr5Si3 nanosheets with good morphology and controllable thickness can be obtained. The controllability of the thickness of Cr5Si3 non-layered materials provides a basis for exploring its thickness-related magnetism. Through VSM testing and Hall device testing, the changes in the intensity of magnetic anisotropy of nanosheets of different thicknesses can be explored, and the magnetic changes of Cr5Si3 with changes in thickness can also be observed, and the thickness range of Cr5Si3 where the topological Hall effect appears can be inferred.
Claims
1. A method for preparing a Cr5Si3 non-layered two-dimensional material, characterized in that: CrCl3 powder and pure silicon wafer are heated and volatilized, and Cr5Si3 non-layered two-dimensional materials are formed by chemical vapor deposition on the substrate in a protective carrier gas atmosphere; The mass ratio of the CrCl3 powder to the pure silicon wafer is 0.5:1 to 2:1; The volatilization temperature of the CrCl3 powder is 650 - 770 °C; The volatilization temperature of the pure silicon wafer is 980 ~ 1060 ° C; The temperature of chemical vapor deposition is 980 ~ 1060 ℃.
2. The method for preparing the Cr5Si3 non-layered two-dimensional material according to claim 1, characterized in that: The volatilization temperature of the CrCl3 powder is 710-740°C.
3. The method for preparing the Cr5Si3 non-layered two-dimensional material according to claim 1, characterized in that: The protective carrier gas is at least one of nitrogen and inert gas.
4. The method for preparing the Cr5Si3 non-layered two-dimensional material according to claim 1, characterized in that: During the chemical vapor deposition stage, the flow rate of the protective carrier gas is 10 to 200 sccm.
5. The method for preparing the Cr5Si3 non-layered two-dimensional material according to claim 1, characterized in that: The substrate is a SiO2 / Si substrate.
6. The method for preparing the Cr5Si3 non-layered two-dimensional material according to claim 5, characterized in that: The surface of the SiO2 / Si substrate is composited with SiO2 / Si sheets.
7. The method for preparing the Cr5Si3 non-layered two-dimensional material according to claim 1, characterized in that: The volatilization temperature of the pure silicon wafer is 1010 ~ 1050 °C.
8. The method for preparing the Cr5Si3 non-layered two-dimensional material according to claim 7, characterized in that: The volatilization temperature of the pure silicon wafer is 1020 ~ 1030 °C.
9. The method for preparing the Cr5Si3 non-layered two-dimensional material according to claim 1, characterized in that: The temperature of the chemical vapor deposition stage is 1010 ~ 1050 ℃.
10. The method for preparing the Cr5Si3 non-layered two-dimensional material according to claim 9, characterized in that: The temperature of the chemical vapor deposition stage is 1020 ~ 1030 ℃.
11. The method for preparing the Cr5Si3 non-layered two-dimensional material according to claim 1, characterized in that: The temperature difference between volatilization and chemical vapor deposition of pure silicon wafers is less than or equal to 5°C.
12. The method for preparing the Cr5Si3 non-layered two-dimensional material according to claim 11, characterized in that: The volatilization and chemical vapor deposition temperatures of pure silicon wafers are the same.
13. The method for preparing the Cr5Si3 non-layered two-dimensional material according to claim 1, characterized in that: The chemical vapor deposition time is 2 to 10 min.
14. The method for preparing the Cr5Si3 non-layered two-dimensional material according to any one of claims 1 to 13, characterized in that: The deposition device for implementing the preparation method comprises a sealed quartz tube, one end of which is provided with an inlet for inputting carrier gas into the chamber of the quartz tube, and the other end is provided with an outlet for outputting the gas in the chamber of the quartz tube; according to the direction of the carrier gas flow, the chamber of the quartz tube is divided into an upstream variable temperature zone and a downstream high-temperature constant temperature zone; the high-temperature constant temperature zone is provided with a heating device, a magnetic boat loaded with CrCl3 powder is placed in the upstream variable temperature zone, and a magnetic boat loaded with pure silicon wafers and SiO2 / Si substrates is placed in the downstream high-temperature constant temperature zone; During the preparation process, CrCl3 powder and pure silicon wafers are heated to the volatilization temperature under the action of protective gas as carrier gas, and the temperature of the downstream high-temperature constant temperature zone is controlled within the chemical vapor deposition temperature range, so that the volatilized CrCl3 powder and pure silicon wafer raw materials react with each other and are deposited on the SiO2 / Si substrate, and Cr5Si3 non-layered two-dimensional material is grown on the SiO2 / Si substrate.
15. The method for preparing the Cr5Si3 non-layered two-dimensional material according to claim 1, characterized in that: The thickness of the Cr5Si3 non-layered two-dimensional material is 3.8 - 45 nm.
16. The method for preparing the Cr5Si3 non-layered two-dimensional material according to claim 15, characterized in that: The thickness of the Cr5Si3 non-layered two-dimensional material is 13 to 35 nm.
17. The method for preparing the Cr5Si3 non-layered two-dimensional material according to claim 16, characterized in that: The thickness of the Cr5Si3 non-layered two-dimensional material is 14 to 20 nm.
18. An application of the Cr5Si3 non-layered two-dimensional material obtained by the preparation method according to any one of claims 1 to 17, characterized in that: It is used to prepare Hall devices.
Citation Information
Patent Citations
Controllable preparation method for silicideb nanometer belts / nanometer sheets
CN101560694A